Hak Preferen Kreditor Melaksanakan Lelang Eksekusi Jaminan Fidusia - Simbolon, Fransiska Agustina; Kamello, Tan; Sidabariba, Burhan; Andriati, Syarifah Lisa (Universitas Gorontalo, 2025)
This research discusses the preferential rights of creditors in the implementation of fiduciary security execution auctions in Indonesia, as well as the impact of the Constitutional Court decision No. 18/PUU-XVII/2019 on these rights. Prior to the decision, creditors could execute fiduciary security objects without going to court. However, the Constitutional Court's decision changed the mechanism by requiring the debtor's consent or a court decision. This research uses normative legal research methods with a case and statutory approach. The results show that the Constitutional Court's decision aims to protect debtors' rights from creditors' arbitrary actions, although it also creates legal uncertainty for creditors.